A Quality Improvement Initiative to Increase Scoring Consistency and Accuracy of the Finnegan Tool: Challenges in Obtaining Reliable Assessments of Drug Withdrawal in Neonatal Abstinence Syndrome. (February 2018) - Timpson, Wendy; Killoran, Cheryl; Maranda, Louise; Picarillo, Alan; Bloch-Salisbury, Elisabeth
Abstract : Background: Current practice for diagnosing neonatal abstinence syndrome and guiding pharmacological management of neonatal drug withdrawal is dependent on nursing assessments and repeated evaluation of clinical signs. Purpose: This single-center quality improvement initiative was designed to improve accuracy and consistency of Finnegan scores among neonatal nurses. Methods: One-hundred seventy neonatal nurses participated in a single-session withdrawal-assessment program that incorporated education, scoring guidelines, and a restructured Finnegan scale. Nurses scored a standardized video-recorded infant presenting with opioid withdrawal before and after training. Results: Nearly twice as many nurses scored at target (Finnegan score of 8) posttraining (34.7%; mean error = 0.559, SD = 1.4) compared with pretraining (18.8%; mean error = 1.31, SD = 1.95; Wilcoxon, P < .001). Finnegan scores were significantly higher than the target score pretraining (mean = 9.31, SD = 1.95) compared with posttraining (mean = 8.56, SD = 1.40, Wilcoxon P < .001); follow-up assessments reverted to pretraining levels (mean = 9.16, SD = 1.8). Score dispersion was greater pretraining (variance 3.80) compared with posttraining (variance 1.96; Kendall's Coefficient, P < .001) largely due to score disparity among central nervous system symptomology. Implications for Practice: Education, clinical guidelines, and a restructured scoring tool increased consistency and accuracy of infant withdrawal-assessments among neonatal nurses. However, more than 60% of nurses did not assess withdrawal to the target score immediately following the training period and improvements did not persist over time. Implications for Research: This study highlights the need for more objective tools to quantify withdrawal severity given that assessments are the primary driver of pharmacological management in neonatal drug withdrawal. Video Abstract available at https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx . Abstract : Supplemental Digital Content is Available in the Text.